A study of process optimization of carburetor die casting process. (2022) - Gupta, Rahul Dev; Sharma, Neeraj; Khanna, Rajesh; Sharma, Sammer; Dayal, Sunny
Abstract: Die-casting is a multipurpose practice for casting metallic components in high volume by pouring metal at high pressure into metal molds. In the present study, zinc based alloys having high ductility, impact strength and can be easily plated, are used to cast the carburetor. Zinc based alloys are also easy to cast, economical for small parts, good die life and low melting point. Defects arising in castings are mainly depends upon the solidification process and the intermediate temperature profiles, as the temperature gradients inside the casting will decide that a section in solidification stage has availability to necessary quantity of higher temperature molten metal. The consequences of die casting process parameters has not been deliberated widely to minimise the defects like tear out & misrun. The present work has been carried out to minimize the rejection rate due to these casting defects in die casting process of zinc alloy by adjusting parameters, molten metal temperature and time needed for solidification. During analyzing the previous data of production of castings, it was noticed that the Mixing Chamber Body of carburetors had a rejection rate of about 14–15%, but with the use of design of experiments using Taguchi method this rejection rate is reduced to 6.7%. ANOVA is used to specify the significant factors and solidification time has 92.5% contribution to minimize the defects. Confirmatory test performed at these optimal settings concluded that within 95% confidence interval casting defects were minimum. As the solidification time increases number of casting rejection rate decreases rapidly and at 6 s performed better result with lesser no. of defects and hence more effective.